GE_GERICHTE A/2490/2018 vom 13. September 2018 - GE Cour de justice (2018)
Gage immobilier estimation expertise avis spécial liquidation sommaire de la faillite | LP.230a.al2; LP.230a.al4; LP.257; LP.140.al3; ORFI.9.al2; OAOF.71